Role of Tetraspanins in Hepatocellular Carcinoma - Cai, Sicheng; Deng, Yue; Peng, Huiming; Shen, Jian (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is characterized by high prevalence, morbidity, and mortality. Liver cancer is the sixth most common cancer worldwide; and its subtype, HCC, accounts for nearly 80% of cases. HCC progresses rapidly, and to date, there is no efficacious treatment for advanced HCC. Tetraspanins belong to a protein family characterized by four transmembrane domains. Thirty-three known tetraspanins are widely expressed on the surface of most nucleated cells and play important roles in different biological processes. In our review, we summarize the functions of tetraspanins and their underlying mechanism in the life cycle of HCC, from its initiation, progression, and finally to treatment. CD9, TSPAN15, and TSPAN31 can promote HCC cell proliferation or suppress apoptosis. CD63, CD151, and TSPAN8 can also facilitate HCC metastasis, while CD82 serves as a suppressor of metastasis. TSPAN1, TSPAN8, and CD151 act as prognosis indicators and are inversely correlated to the overall survival rate of HCC patients. In addition, we discuss the potential of role of the tetraspanin family proteins as novel therapeutic targets and as an approach to overcome drug resistance, and also provide suggestions for further research.